Unraveling Home Protection in the IoT Age: Living, Mixed Reality, and Home 2.0 - Zhao, Bo (Science and Technology Law Review, 2020)
Walls, windows, roofs, and fences cannot protect our home from virtual invasions and other non-physical intrusions. Neither can the current legal framework of home protection continue to safeguard the sanctity of home in a data- driven environment. Due to critical changes in household infrastructure and lifestyle, contemporary law has gradually become disconnected from the reality of the digital home, providing less protection than it did in the pre-digital age. This is partially because contemporary law has not properly addressed the complications, including a) the rise of digital and hybrid spaces and digital assets in the traditional physical home; b) the fast expansion of home (private) life into multiple spaces and places independent of geo-location; c) the lack of clear home boundaries in the digital world, as compared to boundaries previously marked by physical walls, fences, windows, etc.; d) the new power dynamics between home residents (now the data source) and devices and services providers (now increasingly in control of the home); e) the growing significance of home data protection in addition to physical privacy; f) the changing perception of home in the Internet of Things (IoT) age that is becoming more detached from home’s geo- location and physical features; and g) weak enforcement jurisdiction in view of the complicated industrial supply chain, growing cross-border data flows, and untamed foreign tech powers. This paper argues that contemporary law needs to develop a better conceptual framework to adjust to the fundamental changes as outlined. It argues that the inviolability of the home and home protection should cover not only the home’s physical space, but also its virtual and hybrid space, helping residents regain their control of home. This can be achieved, the paper suggests, by adopting a new concept “Home 2.0,” an upgrade of the traditional home (“Home 1.0”), and by re-emphasizing the physicality of the new home environment to better anchor the current home protection legal framework.